Herpes virus 6 hepatitis in an infant - L.A. Khodak; V.I. Brailko; L.V. Mushenko (Zaslavsky O.Yu., 2017)
The article presents a clinical observation of 1-year old child diagnosed with hepatitis in the structure of reactivated form of herpes virus type 6 infection. There was a significant increase in transaminase level with other normal biochemical parameters of the liver. The effect of the administration of antiviral therapy with acyclovir intravenously was obtained.